2022
DOI: 10.3390/jcm11154490
|View full text |Cite
|
Sign up to set email alerts
|

Liver Function Tests in COVID-19: Assessment of the Actual Prognostic Value

Abstract: Deviations in laboratory tests assessing liver function in patients with COVID-19 are frequently observed. Their importance and pathogenesis are still debated. In our retrospective study, we analyzed liver-related parameters: aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), gamma-glutamyltransferase (GGT), total bilirubin (TBIL), albumin, comorbidities and other selected potential risk factors in patients admitted with SARS-CoV-2 infection to assess their prognostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…They found that elevated ALT, AST, and total bilirubin levels, but not elevated alkaline phosphatase levels, were associated either with COVID-19 mortality or risk of intubation. In another study from Poland involving 2184 patients, only an elevated AST level was associated with COVID-19-related mortality [ 26 ]. In this analysis too, alkaline phosphatase was not associated with COVID-19 outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…They found that elevated ALT, AST, and total bilirubin levels, but not elevated alkaline phosphatase levels, were associated either with COVID-19 mortality or risk of intubation. In another study from Poland involving 2184 patients, only an elevated AST level was associated with COVID-19-related mortality [ 26 ]. In this analysis too, alkaline phosphatase was not associated with COVID-19 outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Liver enzyme abnormalities are frequent in patients with COVID-19 infection, and they are associated with disease severity[ 18 , 38 ]. The most frequently reported mild to moderate elevations were in aspartate aminotransferase (ALT), alanine aminotransferase (AST), and total bilirubin (tBIL) levels[ 35 ], but abnormal gamma-glutamyl transferase (GGT), alkaline phosphatase (ALP), and albumin levels have been found in patients with COVID-19 as well[ 18 , 22 , 39 ]. Liver damage in COVID-19 is usually temporary, and therefore, the enzyme levels of most patients usually return to normal after recovery[ 18 , 40 ].…”
Section: Prognostic Factors In Covid-19 Patients With Liver Diseasementioning
confidence: 99%
“…Although, Săbiescu et al [ 76 ] proved that only elevation over five times the upper limit is strongly correlated with high mortality risk. Also, hypoalbuminemia is a strong predictor of severe COVID-19 course and, in combination with AST or total bilirubin (TBIL), has a remarkable association with mortality[ 77 ], even in patients without chronic illness[ 78 ]. Furthermore, Da et al [ 79 ] reported a correlation between ALT levels and levels of inflammatory markers such as C-reactive protein, D-dimers, ferritin, and IL-6.…”
Section: Liver Manifestations Associated With Covid-19mentioning
confidence: 99%